TET1 methylation is associated with childhood asthma and traffic-related air pollution - Somineni, Hari K. (J Allergy Clin Immunol, 2015)
BACKGROUND: Asthma is a complex disorder influenced by genetics and the environment. Recent findings have linked abnormal DNA methylation in T cells with asthma; however, the potential dysregulation of methylation in airway epithelial cells is unknown. Studies of mouse models of asthma have observed greater levels of 5-hydoxymethylcytosine (5-hmC) and TET1 expression in lungs. TET proteins are known to catalyze methylation through modification of 5-mC to 5-hydroxymethylcytosine (5-hmC). OBJECTIVE: Associations between TET1 methylation and asthma and traffic-related air pollution were examined. METHODS: TET1 methylation levels from DNA derived from nasal airway epithelial cells collected from 12 African-American children with physician-diagnosed asthma and their non-asthmatic siblings were measured using Illumina 450K arrays. Regions of interest were verified by locus-specific pyrosequencing in 35 additional sibling pairs and replicated in an independent population (N=186). Exposure to traffic-related air pollution (TRAP) at participants’ early life and current home addresses was estimated using a land-use regression model. Methylation studies in saliva, PBMCs, and human bronchial epithelial cells (HBEC) were done to support our findings. RESULTS: Loss of methylation at a single CpG site in the TET1 promoter (cg23602092) and increased global 5hmC was significantly associated with asthma. In contrast, TRAP exposure at participants’ current homes significantly increased methylation at the same site. Patterns were consistent across tissue sample types. 5-aza-2'-deoxycytidine and diesel exhaust particle exposure in HBEC was associated with altered TET1 methylation, expression and global 5-hmC. CONCLUSIONS: Our findings suggest a possible role of TET1 methylation in asthma and response to TRAP. CAPSULE SUMMARY: TET1 DNA methylation might serve as a biomarker for asthma and higher risk of exposure-related asthma exacerbations.